The Earth's mantle : (Cambridge University Press, 1998)
Interdisciplinary in scope, The Earth's Mantle is a comprehensive overview of the composition, structure and evolution of the mantle layer that strikes a balance between established consensus and continuing controversy. Written by internationally recognized scientists, the book provides an authoritative review of this important part of our planet.